Harvesting Quota and Financial Feasibility of Timor Deer Captive Breeding in Sadhana Arifnusa East Lombok - Ilham, Yopin Okta; Masy'ud, Burhanuddin; Rahman, Dede Aulia (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
Timor deer breeding activities as a type of animal that has economic value have been widely carried out in Indonesia. However, management in the form of determining harvest quotas that affect the feasibility of business is still minimal in various captive Timor deer in Indonesia.The objective of this research were to determine the harvest quota of timor deer and finansial feasibility of cavtive breeding of Sadhana Arifnusa. The harvest quota which is carried out once a year is determined based on the calculation of the break even point (BEP). The scenario of harvesting twice a year is based on the growth rate, and population harvesting rate. Financial feasibility is measured based on investment appraisal criteria, namely Net Present Value, Benefit Cost Ratio, Internal Rate of Return, and Payback Period. The result revealed that the harvest quota which is carried out once a year were 5 individuals, population size that must be available at the time of harvest is 48 individuals. Meanwhile, the harvest quota that is carried out twice a year from year 1 to year 3 is 2 individuals. Based on the financial value of the scheme without slaughter and the scheme with slaughter, it can be said that the timor deer captive business potentially profitable and feasible to develop with NPV values ​​of Rp. 428,748,935 and Rp. 934,136,423 respectively; BCR value respectively 1.66 and 2.46; IRR value of 28.89% and 32.89% respectively, and ability to return investment after 4.6 years and 5.1 years.